Faaliyah Thariqah Qiraah Al Jahriyyah Ala Maharah Al-Qiraah Lada ‎Thalabah Shaff Al Asyir Bi Al-Madrasah Al-Aliyah Al- Islamiyyah Al-‎Hukumiyyah Madinah Solok - Messy Anggraini (Lisaanuna Ta`lim Al-Lughah Al-Arabiyah: Jurnal Pendidikan Bahasa Arab, 2023)
The main problem in this research is “does reading aloud method effective ‎for the reading skills of Tenth Grade Students of Senior High School in ‎Solok City?”. This research is very broad, the author limits the first is ‎students reading ability before using the reading aloud method. second is ‎the using of reading aloud method for the reading skills. third is the ‎effectiveness of the reading aloud method on the reading skills. The purpose ‎of this research is to describe reading ability before using the reading aloud ‎method, to describe using of reading aloud method for the reading skills, to ‎describe the effectiveness of the reading aloud method on the reading skills ‎of Tenth Grade Students . The research method used is quantitative study ‎approach that is quasi eksperimen‏ ‏method and analytic data use SPSS. The ‎result in this research is first the ability before use reading aloud method in ‎control class is 59,28, and eksperimental class is 61,51. second is the using ‎reading aloud method in three steps. first is opening, second is mian activity ‎its five steps observing, asking, trying, associating, and communicating, ‎third is closing. third is the effectiveness of the reading aloud method in ‎eksperimental class is 85,80 and control class is 79,82. and based on result of ‎Paired Sample T test, T table 3,293. and sig(2-Tailed) 0,001 bigger than ‎‎0,000. its mean reading aloud method effective for the reading skills of ‎Tenth Grade Students of Senior High School in Solok City